Effects of acute aerobic exercise on response preparation in a Go/No Go Task in children with ADHD: An ERP study - Lan-Ya Chuang; Yu-Jung Tsai; Yu-Kai Chang; Chung-Ju Huang; Tsung-Min Hung (Elsevier, 2015)
Purpose: The purpose of this study was to investigate the impact of acute exercise on reaction time and response preparation during a Go/No Go Task in children with attention deficit hyperactivity disorder (ADHD). Methods: Nineteen children with ADHD (aged between 8 and 12 years old) undertook a 30-min intervention that consisted of treadmill running or video-watching presented in a counterbalanced order on different days. A Go/No Go Task was administrated after exercise or video-watching. Results: The results indicated a shorter reaction time and smaller contingent negative variation (CNV) 2 amplitude following exercise relative to the video-watching. For event related potential (ERP) analyses, greater CNV 1 and CNV 2 amplitudes in response to No Go stimuli in comparison to Go stimuli was observed in the video-watching session only. Conclusion: These findings suggest that acute exercise may benefit children with ADHD by developing appropriate response preparation, particularly in maintaining a stable motor preparatory set prior to performing the given task.